Gifts of an Uncommon Life: The Practice of Contemplative Activism - Friend, Howard E. (Rowman & Littlefield Publishers, 2008)
This book of ten essays is a breath of fresh air, a source of inspiration, a wake-up call, and a bold challenge for pastors, congregational leaders, and church members--both active and lapsed--who long for a new perspective, even a touch of creative irreverence. With an invitation to quietness and stillness, inner strength and resilience, audacious hope and insistent confidence, it welcomes those among the people of God who do not belong to a church or even name themselves as Christian. Yet it does not shy away from raising difficult questions. Howard Friend offers forthright, at times disarming, candor as he shares his personal pilgrimage of activism rooted in contemplation. Convinced that God still seeks to work in and through the church, Friend shows us where God is present--at times despite the church itself. In his opinion, the church needs to stir the pot, upset the applecart, and dare to welcome the new and refreshing. Yet Friend remains hopeful for and committed to the church, calling and equipping it to become its highest and best. Drawing on a range of stories from the Bible and his own lived experiences, Friend invites us to meet real people--pastors, leaders, everyday folks--who dare to dream a new dream, journey toward a far horizon, walk with tireless determination, and press on with awesome hope.